Hints and solutions manual for part a problems [for] Mathematics for elementary teachers : a contemporary approach - Trimpe, Lynn E.; ... [et al.] (New York ; Chichester : John Wiley and Sons, 2000)
Hints for part a problems. Solutions to part a problems.
Keywords: Education; Mathematics; Mathematics -- Study and Teaching (Elementary); Mathematics